1999
DOI: 10.1590/s0103-50531999000600013
|View full text |Cite
|
Sign up to set email alerts
|

PS-HEMA latex fractionation by sedimentation and colloidal crystallization

Abstract: Látex de poli(estireno-co-hidroxiacrilato de metila) separa-se em três camadas visualmente distinguíveis, das quais a inferior é opalescente e contém cristais coloidais. Alíquotas do látex foram coletadas em diferentes alturas, e as partículas foram caracterizadas, por espalhamento de luz dinâmico, microeletroforese, IV e microscopia eletrônica analítica. A fração inferior contém a maior parte do polímero, sendo formada por partículas de dimensões e composição química uniformes. As partículas coletadas das dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Since this void volume is occupied by swollen polymer, we can use this as a lower limit for the swelling coefficient of the particles. Such a figure may appear very large, but we recall that a 50% volume increase for spheres corresponds to a 15% increase in the radius only, and this in less than the difference between PS-HEMA swollen and dry particle diameters as determined by PCS (423 nm) and transmission electron microscopy (319 nm) (13). Moreover, the inner macrocrystal layers should also swell, and this will contribute to further effects on film structure, but in a longer time scale.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Since this void volume is occupied by swollen polymer, we can use this as a lower limit for the swelling coefficient of the particles. Such a figure may appear very large, but we recall that a 50% volume increase for spheres corresponds to a 15% increase in the radius only, and this in less than the difference between PS-HEMA swollen and dry particle diameters as determined by PCS (423 nm) and transmission electron microscopy (319 nm) (13). Moreover, the inner macrocrystal layers should also swell, and this will contribute to further effects on film structure, but in a longer time scale.…”
Section: Discussionmentioning
confidence: 80%
“…In the dry microcrystal, we observe two point defects due to the absence of particles. The particles appear as distorted hexahedra, and this is better seen in the magnified view in other samples, and they depend on the degree of particle chemical heterogeneity (20,21) or on the degree of latex fractionation (13) prior to the preparation of the macrocrystals. These observations show that the comparison of dry and swollen film has to take into account the multiplicity of domains observable in the film surface.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous work, we found that a poly(styrene-cohydroxyethylmethacrylate) latex formed macrocrystals easily (19), and the quality of these orderly particle arrays was much improved by latex fractionation (20). This finding was combined with other results, showing that latex particles are dipoles (21) (or multipoles), which are all aligned in the macrocrystal domains and are thus relevant for particle interaction and selfarraying.…”
Section: Introductionmentioning
confidence: 66%
“…The colloidal particles were synthesized by surfactant-free emulsion polymerization in water with potassium persulfate initiator and no other added ingredients. , The latex formed colloidal crystalline films with exceptional ease. ,, The latex may have contained minor amounts of low molecular weight HEMA-rich soluble polymer and salts derived from the initiator . The TEM and AFM images of the latex showed few or no particles of smaller size or different surface texture, and no attempt was made to remove smaller particles or soluble impurities from the sample.…”
Section: Resultsmentioning
confidence: 99%